Effects of Pre-sowing Treatments on Seed Germination of Oaks in Kumaun, West Himalaya - Meenakshi NEGI (Notulae Scientia Biologicae, 2018)
The noticeable decline in natural regeneration of three important species of west Himalayan oaks, namely Quercus glauca, Q. leucotrichophora and Q. lanuginosa, on account of excessive lopping, over grazing and tree felling accompanied by non-viable seeds due to short viability, extreme weevil and pest infestation, animal and bird predation resulting in low acorn production and thus overall poor natural regeneration is of great concern. A study was therefore, carried out with an objective to find out possibilities of improving germination ability of selected oak species using different pre-sowing treatments on three seed size classes- small, medium and large collected from Nainital region of Uttarakhand. A wide variation in seed size existed within these species and germination was found to vary with seed weight; large and medium size seeds exhibiting higher germination. Under various pre-sowing treatments, seeds from different species did not reflect uniformity in responses. Among all the set of experiments, water soaking (48 h) proved to be the best and cost effective approach by significantly improving seed germination over control, Q. glauca (53.3 to 73.3%), Q. leucotrichophora (66.67 to 90.0%) and Q. lanuginosa (58.33 to 75.0%). However, acid scarification emerges as effective pre-sowing treatment. Both water soaking and acid scarification treatments also helped in reducing Mean Germination Time. The outcomes of this study clearly reflect some of the simple, practical and cost effective methods for mass seedling production and restoration of degraded hills in west Himalaya.